Attempt to save Friendship, or What the Liberator of Prague Did in Czechoslovakia in May 1968 - I. A. Permyakov; S. G. Antonenko (Vestnik MGIMO-Universiteta)
The article introduces the publication of the recently declassified archival documents of the Russian State Archive of Contemporary History (RGANI) and the Archive of Foreign Policy of the Russian Federation concerning the stay of a delegation of Soviet military leaders in the Czechoslovak Socialist Republic on May 8-14, 1968, led by Marshal of the Soviet Union I.S. Konev. In August 2018, at the initiative of the Prague 6 City Council, metal “information plates” were installed on the pedestal of the monument to Marshal Konev, where among other things it was stated that “In 1968, he personally backed the intelligence surveillance preceding the invasion of the armed forces of the Warsaw Pact into Czechoslovakia". This action was part of measures to prepare public opinion for the removal of the monument. The documents being published show there is not the slightest reason to consider the soviet delegation headed by Marshal Konev as intelligence surveillance operation to prepare for an invasion. The internal political crisis in Czechoslovakia in early May had not yet reached its peak (the famous manifesto "Two Thousand Words" will be published only on June 27). The Soviet leadership, headed by L. Brezhnev hoped that the "Czechoslovak comrades" would be able to cope with the situation, "would rebuff the anti-socialist forces." The delegation of the Soviet military leaders had a symbolic, cultural significance and was intended to revive the memory of the events of 1945, of the victims of the Red Army and the brotherhood in arms of Soviet and Czechoslovak soldiers. In the extremely unstable and confused atmosphere of the “Prague Spring”, the members of the delegation sought to clarify the true state of affairs and public sentiments in the country. As Marshals Konev and Moskalenko admitted themselves, they “had no opportunity to fully understand all the processes”. The so-called "intelligence surveillance", which is mentioned in the Czech press, was carried out by them in a completely open way of meeting and exchanging views with colleagues, speaking at rallies, and communicating with workers. Moscow preferred to act at the time by political methods, gradually shifting to military pressure (the “Shumava” military exercises). The time for tough demands came later (negotiations in Čierna nad Tisou, July 29 – August 1, and in Bratislava on August 3, 1968). The final decision on the intervention was made by the Soviet political leadership after numerous consultations with partners in the socialist camp, largely under the influence of the tough position of the first secretary of the PUWP Central Committee W. Gomulka and the first secretary of the SED Central Committee V. Ulbricht.